2012
DOI: 10.2527/jas.2011-3496
|View full text |Cite
|
Sign up to set email alerts
|

Administration of estradiol, trenbolone acetate, and trenbolone acetate/estradiol implants alters adipogenic and myogenic gene expression in bovine skeletal muscle

Abstract: Twenty crossbred yearling steers (421 kg) were used to evaluate the effects of implanting with trenbolone acetate (TBA; 120 mg), estradiol-17β (E(2); 25.7 mg), and a combination (120 mg of TBA and 24 mg of E(2)) on adipogenic and myogenic mRNA concentrations. Animals were blocked by BW and within each block were assigned to 1 of 4 treatments. Animals were housed and fed in individual pens with 5 animals per treatment. All animals were weighed weekly, and muscle biopsy samples were taken from the LM of each ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Other studies of bovine adipose tissue explants (Hosseini et al, 2010) and bovine liver (Janovick-Guretzky et al, 2007) also demonstrated that RPS9 mRNA expression was stable and suitable as a normalization gene under their conditions. Additionally, RPS9 was used as a normalization gene for the expression of genes in bovine muscle (Baxa et al, 2010;Chung et al, 2011).…”
Section: Rna Extraction and Real-time Polymerase Chain Reactionmentioning
confidence: 99%
“…Other studies of bovine adipose tissue explants (Hosseini et al, 2010) and bovine liver (Janovick-Guretzky et al, 2007) also demonstrated that RPS9 mRNA expression was stable and suitable as a normalization gene under their conditions. Additionally, RPS9 was used as a normalization gene for the expression of genes in bovine muscle (Baxa et al, 2010;Chung et al, 2011).…”
Section: Rna Extraction and Real-time Polymerase Chain Reactionmentioning
confidence: 99%
“…Serum was then obtained by centrifugation (1 500 × g, for 20 min at 4 °C), divided into aliquots and stored at −20 °C until use. Steer management, including diet and implantation protocol, were identical to a companion study reported previously (Chung et al, 2012). In brief, the diet was a steam flaked maize and ground lucerne hay based diet that provided (dry matter basis) 135.6 g crude protein, 141.5 g neutral detergent fibre, 19.3 MJ NE m /kg and 13.1 MJ NE g /kg.…”
Section: Methodsmentioning
confidence: 99%
“…Results agree with similar studies that reported increased percentage USDA Prime or Choice and decreased percentage of USDA Select in steers administered lower or delayed potencies of TBA ( Parr et al, 2011 ; Kayser et al, 2019 ; Quinn et al, 2020 ). Other researchers have reported detrimental effects of TBA on marbling development ( Chung et al, 2012 ; Smith et al, 2017 ).…”
Section: Resultsmentioning
confidence: 89%